Comparative Analysis of Electrostatic Charging Characteristics Considering the Flow Conditions of Nonconductive Flammable Liquids - Junghwan Byeon; Hyeongon Park; Woong Ko (Energies)
Electrostatic is generated through friction or contact between certain materials—a process that frequently occurs in industries such as manufacturing, logistics, electronics, chemicals, petroleum, and gas. In particular, in industries dealing with flammable materials—such as petrochemicals, refining, energy, semiconductors, and electronics—electrostatic can pose a fire or explosion risk, highlighting the critical importance of implementing electrostatic control and preventive measures. To manage electrostatic at a safe level, it is crucial to prevent charge accumulation that would lead to high charging voltages. This study developed a streaming electrification generator that considers the flow conditions of non-conductive flammable liquids, allowing observation, comparison, and analysis of electrostatic charging characteristics. Specifically, to determine conditions that create fire and explosion hazard atmospheres, measurements of charging voltage, discharging current, and charging electric charge were obtained and analyzed under various experimental conditions. A comparative analysis of various electrostatic charging characteristics revealed that, in certain cases, increasing the temperature of a flowing liquid may actually decrease the charging voltage depending on the properties of the pipeline material. By considering not only the decrease in liquid conductivity with temperature changes but also the variation in the work function of solid materials, the underlying causes of the observed results can be understood. The experimental results derived from this study provide concrete and reliable data essential for controlling and managing electrostatic at a safe level and are expected to serve as a foundational resource to more clearly identify electrostatic risks in industrial safety management.